Stress, coping profiles, and depression among nurses: a latent profile and mediation analysis - Ping-Zhen Lin; Li-Hui Yang; Jing Su; Jiao-Mei Xue (BMC Nursing)
Abstract Background Stress is significantly associated with depressed mood in nurses. However, it remains unclear whether the mechanisms by which two types of stress—childhood adversity and perceived stress—affect depression are identical. This study aims to investigate the relationship between stress (including childhood adversity and perceived stress) and depression, as well as the mediating role of coping profiles. Methods A survey was conducted among 737 nurses in a tertiary hospital in China using the Revised Adverse Childhood Experiences Questionnaire, the Perceived Stress Scale, the Trait Coping Styles Questionnaire, and the Patient Health Questionnaire-9. Latent profile analyses were performed using Mplus, and mediation analyses were conducted using R software. Results Coping profiles were categorized into four groups: “Low Coping” (9.9%), “Inadequate Coping” (39.5%), “Emotional Suppression” (32.0%), and “Active Coping” (18.6%). Both childhood adversity and perceived stress were positively associated with depression levels in nurses. The “Emotional Suppression” profiles played a mediating role in the relationship between childhood adversity and depression. “Emotional Suppression” and “Low Coping” profiles played mediating roles in the relationship between perceived stress and depression. Conclusions Stress and coping profiles are established risk factors of depression among nurses. Reducing stress levels and improving coping profiles among nurses can have a substantial impact on the prevention and alleviation of depression.